2010
DOI: 10.1017/s0144686x10000140
|View full text |Cite
|
Sign up to set email alerts
|

Why do older adult volunteers stop volunteering?

Abstract: This paper reports a United States study of the factors that influence the turnover of older adult volunteers. Based on a parent study of programmes that use older adult volunteers, the follow-up study examined the experience for 207 older volunteers who served in ten programmes in 2005 and 2006, respectively. Telephone interviews and mail surveys were used to collect programme and personal information. The findings indicated that aspects of the volunteer experience, like duration of involvement, volunteering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 31 publications
(37 reference statements)
3
51
0
5
Order By: Relevance
“…42 These strategies have been shown to be helpful for enhancing participation somewhat, but are minimally associated with sustained volunteer engagement. 43 Compensation was proposed to increase sustained engagement speci½cally of under represented groups, but researchers dis covered that all older adults-regardless of socioeconomic status-½nd the stipend important. This is for two reasons: 1) most elderly are on a ½xed income, and the small stipend covers out of pocket costs of volunteering; and 2) a stipend lends credibility to the program, since it demonstrates that organizers believe its impact is worth the ½nancial investment.…”
Section: Productivity and Engagement In An Agingmentioning
confidence: 99%
“…42 These strategies have been shown to be helpful for enhancing participation somewhat, but are minimally associated with sustained volunteer engagement. 43 Compensation was proposed to increase sustained engagement speci½cally of under represented groups, but researchers dis covered that all older adults-regardless of socioeconomic status-½nd the stipend important. This is for two reasons: 1) most elderly are on a ½xed income, and the small stipend covers out of pocket costs of volunteering; and 2) a stipend lends credibility to the program, since it demonstrates that organizers believe its impact is worth the ½nancial investment.…”
Section: Productivity and Engagement In An Agingmentioning
confidence: 99%
“…In addition, Morrow-Howell et al (2009) indicate that stipends are associated with benefits to volunteers, their families, and their communities. Tang et al (2010b) note that a lack of stipends is a reason for volunteer turnover. Similarly, McBride et al (2011) suggest that volunteers who received a stipend found the stipend to be important, and even critical, to being able to participate.…”
Section: Synthesis Of Best Practicesmentioning
confidence: 99%
“…Few studies have focused on the importance of organizational support in promoting the benefits of volunteering among older adults [42], and organizational support has been described as a neglected factor in research related to voluntary work in general [43]. Although their study was not of older adults, Hildago and Moreno [43] found that the characteristics of the tasks and jobs performed by volunteers were a main predictor of worker satisfaction and motivation.…”
Section: Discussionmentioning
confidence: 99%